Mutation - Smith, Roland, 1951- (New York : Scholastic Press, 2014)
"Marty and his best friend, Luther, have managed to rescue Marty's cousin Grace from the clutches of the nefarious pseudo-naturalist Noah Blackwood, but their most dangerous mission lies ahead of them. Marty's parents have been missing in Brazil for months, and their trail has all but run cold. With time running out, Marty and the Cryptos Island crew race off for Brazil--where they discover that Noah Blackwood has twisted the natural order of things beyond their wildest, most terrifying dreams"--Provided by publisher.
6.4
3-6
7680L
Keywords: Animals, Mythical -- Juvenile fiction; Jungles -- Juvenile fiction; Missing persons -- Juvenile fiction; Animals, Mythical -- Fiction; Jungles -- Fiction; Missing persons -- Fiction; Adventure and adventurers -- Fiction; Mythical animals -- Fiction; Jungles -- Fiction; Missing persons -- Fiction; Adventure fiction; Adventure and adventurers -- Fiction; Animals, Mythical -- Fiction; Jungles -- Fiction; Missing persons -- Fiction; Brazil -- Juvenile fiction; Brazil -- Fiction; Brazil -- Fiction; Brazil -- Fiction; Adventure fiction